Konflik Batin dan Mekanisme Pertahanan Psikologis: Perspektif Bandingan Psikoanalisis Freud pada Balas Dendam Tokoh Utama Film The Professionals (2016) dan Foxtrot Six (2019) - Shine, Sesilia Angela; Falah, Fajrul (Sabda: Jurnal Kajian Kebudayaan, 2021)
This analysis focuses on the revenge of the main characters in the films "The Professionals" (2016) and "Foxtrot Six" (2019), which will be examined through Sigmund Freud's Psychoanalytic theory based on the id, ego, and superego of the main characters' actions in the films. The qualitative approach employed with a comparative analysis method aims to delve more deeply into understanding and analyzing the psychological aspects of the main characters in both films. This is particularly focused on the context, inner conflicts, psychological defense mechanisms, and revenge motives. The research findings indicate a significant contribution to understanding the psychology of characters in the context of film, urging a deeper consideration of the impact of inner conflicts on the narrative and characters in cinematic works.